2014
DOI: 10.1634/theoncologist.2013-0244
|View full text |Cite
|
Sign up to set email alerts
|

Touching the Other's Suffering: Cross-Cultural Challenges in Palliative Treatment Along Geopolitical Crossroads

Abstract: The authors describe the cross‐cultural considerations in caring for a Palestinian breast cancer patient by an Israeli heath care team. The processes that facilitated a metamorphosis from possible hostility to receptiveness based on historical cultural conflicts were rooted in professionalism, patient‐centered care, and cross‐cultural sensitivity, woven into the patient's own health beliefs and affinity to traditional Islamic medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Yet within the Israeli healthcare environment, there is a separation between patient care and military matters, where healthcare professionalism is split apart from nationality and politics (Nehari, Bielorai, & Toren, ). While no study was found that has produced "scientific evidence" that healthcare providers give unbiased care regardless of ethnicity, several case reports have been published that describe healthcare workers and nursing students from different backgrounds working side by side to care for all (Arieli & Hirschfeld, ; Benari, ; Ben‐Arye, Silbermann, Dagash, Shulman, & Schiff, ; Levy, ; Nehari et al., ). Jotkowitz and Sofer () have termed the provision of appropriate care to all in need, irrespective of personal beliefs as “ethical caring.” They describe Israeli hospitals admitting terrorists and their victims, with all receiving appropriate medical care.…”
mentioning
confidence: 99%
“…Yet within the Israeli healthcare environment, there is a separation between patient care and military matters, where healthcare professionalism is split apart from nationality and politics (Nehari, Bielorai, & Toren, ). While no study was found that has produced "scientific evidence" that healthcare providers give unbiased care regardless of ethnicity, several case reports have been published that describe healthcare workers and nursing students from different backgrounds working side by side to care for all (Arieli & Hirschfeld, ; Benari, ; Ben‐Arye, Silbermann, Dagash, Shulman, & Schiff, ; Levy, ; Nehari et al., ). Jotkowitz and Sofer () have termed the provision of appropriate care to all in need, irrespective of personal beliefs as “ethical caring.” They describe Israeli hospitals admitting terrorists and their victims, with all receiving appropriate medical care.…”
mentioning
confidence: 99%